2017
DOI: 10.1007/s11743-017-1952-x
|View full text |Cite
|
Sign up to set email alerts
|

Waste Cooking Oil‐Based Novel Gemini Imidazolinium Surfactants With Carbonate Linkage: Green Synthesis, Characterization and Properties Evaluation

Abstract: Imidazolinium surfactants belong to the category of cationic surfactants that have already gained the great interest of researchers due to their varied range of commercial applications. With the advancement in the field of surfactants research, imidazolinium surfactants are being converted into their corresponding gemini surfactants. Gemini surfactants are known to have exceptional selfassembling characteristics and exclusive interfacial activity that include much lower CMC and better ability to reduce surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…Moran and others found that the behavior of amino acid-based GSs showed better surface and aggregation properties in comparison to similar surfactants of monomeric nature. Performance evaluation of dimeric surfactants showed superiority in terms of surface tension, foaming, emulsification ability, and lime soap dispersibility as reported in earlier studies. , Green synthesis and characterization properties of GSs from waste cooking oil were investigated with improved surface active properties, showing a major stride in recycling sector for the manufacture of surface-active agents . Recently, Hussain et al reported the characterization properties of novel amino-amide GSs with low CMC values, surface tension reduction properties, and thermal stability, confirming their potentiality in oil recovery operations.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Moran and others found that the behavior of amino acid-based GSs showed better surface and aggregation properties in comparison to similar surfactants of monomeric nature. Performance evaluation of dimeric surfactants showed superiority in terms of surface tension, foaming, emulsification ability, and lime soap dispersibility as reported in earlier studies. , Green synthesis and characterization properties of GSs from waste cooking oil were investigated with improved surface active properties, showing a major stride in recycling sector for the manufacture of surface-active agents . Recently, Hussain et al reported the characterization properties of novel amino-amide GSs with low CMC values, surface tension reduction properties, and thermal stability, confirming their potentiality in oil recovery operations.…”
Section: Introductionsupporting
confidence: 58%
“…Studies show that the structure of nonionic GSs has an effect on surfactant efficacy . In addition, nonionic gemini systems, especially those synthesized using natural resources, show cost-effectiveness and an environmentally friendly nature, in addition to achieving improved interfacial and bulk aggregation properties. , Other known advantages of employing surfactants of this nature are identified as adaptability in a wide range of systems such as foams, emulsions, and aqueous formulations. , These properties have contributed toward a demand to create novel GSs with potentiality in crude oil displacement studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation